Microcomputer Aided Frequency Stabilization of He-Ne Laser at Absorption Line of 127I2 - KAWABATA, Shoichi; TANAKA, Keiichi (Rēzā kenkyū, 1985)
A new servo-control system is described which employs a 16-bits microcomputer for stabilizing a frequency of 633 nm He-Ne laser on one of hyperfine components of an absorption line of 127I2. The computer controls the laser to do frequency scanning, finds a specified component and stabilizes the frequency of the laser on the component. The computer controls an A/D converter to repeat sampling, which takes 16 sample values at each sampling, from the third derivative of the laser output, and processes them to find the absorption signal and to stabilize the laser. The experiment shows that the stability of the laser is 2.4×10-10 which is evaluated by a variance of the frequency fluctuation.